Effectiveness Of Arabic Learning With Verbal Methods Virtually In Improving Reading And Writing Skills On Arabic Letters: A Case Study On Students Class 1 At Mi Nurul Islam Simpar-Subang - Prahardik, Septian Eka; Sari, Wulan Ratna; Dasuki, Ahmad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Abstract: This study aims to find out how the implementation of Arabic learning with verbal methods in improving students' reading and writing skills in Arabic letters, and to find out how the effectiveness of Arabic learning with verbal methods virtually in improving students' reading and writing skills in Arabic letters, and is there any barriers and supports for the effectiveness of learning Arabic with virtual verbal methods in improving students' ability to read and write Arabic letters. at MI Nurul Islam Simpar Subang. In this modern way, children are taught various languages ranging from everyday language to foreign languages, one of which is Arabic. In order to improve the ability to read and write Arabic letters, it is necessary to use an appropriate method and in accordance with the characteristics of the child. And with this virtual learning, vocabulary mastery with verbal media will be able to develop the ability to read and write Arabic letters indirectly, children know and learn new vocabulary that has never been found in themselves. The approach used in this research is a qualitative approach, the method used is a case study, the data collection techniques used are observation, interviews, and documentation. Analysis of the data used is the technical analysis of the Miles and Huberman models, including: data reduction, data presentation, and verification.